Violence Against Children in the Novel 'Misteri Bilik Korek Api' by Ruwi Meita - Puteri Najlah Meylani (Hasanuddin University, 2023)
This study is driven by the dual objectives of comprehensively identifying and elucidating the diverse manifestations of violence against children within Ruwi Meita's novel